Liverpool's Renewed Liberalism: Britain's Third Party in Post-war Merseyside Politics. (1st January 2022) - Collinson, Marc
Abstract : This article disseminates the initial findings of a project examining political change and party politics in post-war Liverpool. Based on a scoping study funded by a HSLC Research Grant, it explores the exceptionalism of the post-war revival of Liberal party support in Liverpool following 1945, Liverpool, before outlining the initial evidence gleaned from a survey of extant party records in regional and institutional repositories. Finally, it advances an initial conclusion of the project, suggesting an alternative interpretation building on scholarship associated with so-called 'new political history'. This encourages a more pluralist understanding of Merseyside political history, avoiding assumptions of a pre-1945 Conservative bastion or a post-war Labour city.